2016
DOI: 10.1016/j.ultsonch.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 4-chloro 2-aminophenol using combined strategies based on ultrasound, photolysis and ozone

Abstract: The present work investigates the degradation of 4-chloro 2-aminophenol (4C2AP), a highly toxic organic compound, using ultrasonic reactors and combination of ultrasound with photolysis and ozonation for the first time. Two types of ultrasonic reactors viz. ultrasonic horn and ultrasonic bath operating at frequency of 20 kHz and 36 kHz respectively have been used in the work. The effect of initial pH, temperature and power dissipation of the ultrasonic horn on the degradation rate has been investigated. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…It is noteworthy that only 4% of solar light is placed in the UV region, while nearly 46% of its spectrum is placed in the visible region which is far abundant. Hence, developing a robust solar-responsive photocatalyst is urgently required for the next-generation of photocatalysts [16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…It is noteworthy that only 4% of solar light is placed in the UV region, while nearly 46% of its spectrum is placed in the visible region which is far abundant. Hence, developing a robust solar-responsive photocatalyst is urgently required for the next-generation of photocatalysts [16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Under moderately acidic conditions, the structural orientation of molecule support the photon attack favorably [30]. It is also important to note that as 4C2AP is highly photo-sensitive [23], higher degradation is obtained under conditions of natural pH, which also correspond to moderately acidic condition. To maintain strongly acidic pH conditions (pH < 5), strong acid (H 2 SO 4 ) was used which possibly creates interference in the photon interaction with the compound (4C2AP) giving lower degradation at pH of 2 and 4 as compared to natural pH.…”
Section: Effect Of Initial Phmentioning
confidence: 96%
“…Barik and Gogate [23] investigated the degradation of 4C2AP using combined processes as ultrasound (US) + UV, UV + O 3 , US + O 3 and US + UV + O 3 and reported that maximum degradation (99.27%) was obtained in the combined approach of US + UV + O 3 after 2 h of treatment. Arora et al [24] investigated biodegradation of 4C2AP and reported complete degradation after 36 h of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Barik and Gogate [17,53] studied the degradation of 4-chloro 2-aminophenol using the combined process of Ultrasound (US) and HC with UV of wavelength 254 nm. In the case of the combined approach of the US with UV, the maximum degradation of 88.42% was reported whereas, the individual approach of US and UV resulted in degradation of 24.17% and 80.8% as the degradation respectively.…”
Section: Combination Of Hc With Uv Photolysismentioning
confidence: 99%